2021
DOI: 10.3389/fpls.2021.634901
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Recombination Suppression Blocks on the Y Chromosome of Date Palm (Phoenix dactylifera)

Abstract: The genus Phoenix includes the fruit producing date palm tree among 14 species that are all dioecious. Females produce the fruit that are high in sugar content and used in multiple countries ranging from North Africa to South Asia, especially from the Phoenix dactylifera, Phoenix sylvestris, and Phoenix canariensis species. While females produce the fruit, understanding of the genetic basis of sex control only began recently. Through genus-wide sequencing of males and females we recently identified three genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The currently available genome assembly of P. dactylifera , Barhee BC4, was obtained using a male (XY) individual ( 10 ), which has likely rendered the assembly of the non-recombining region more difficult than for the autosomes ( 17 ). As the sex-linked region in P. dactylifera shares synteny with a genomic region on the monoecious oil palm ( Elaeis guineensis ) chromosome 10 ( 8 , 9 , 18 , 19 ), we identified the E. guineensis homologs of the genes found to be sex-linked. Indeed, 78% of genes inferred as sex-linked in either P. dactylifera or K. elegans , including 95% of the common sex-linked genes, were positioned in a single region between 43 and 46.1Mb of the E. guineensis chromosome 10 (GK000085.1, EGPMv6 assembly, Fig.…”
Section: Main Textmentioning
confidence: 99%
“…The currently available genome assembly of P. dactylifera , Barhee BC4, was obtained using a male (XY) individual ( 10 ), which has likely rendered the assembly of the non-recombining region more difficult than for the autosomes ( 17 ). As the sex-linked region in P. dactylifera shares synteny with a genomic region on the monoecious oil palm ( Elaeis guineensis ) chromosome 10 ( 8 , 9 , 18 , 19 ), we identified the E. guineensis homologs of the genes found to be sex-linked. Indeed, 78% of genes inferred as sex-linked in either P. dactylifera or K. elegans , including 95% of the common sex-linked genes, were positioned in a single region between 43 and 46.1Mb of the E. guineensis chromosome 10 (GK000085.1, EGPMv6 assembly, Fig.…”
Section: Main Textmentioning
confidence: 99%
“…A 6-Mb region has been further mapped onto the distal end of chromosome 12, which has been found to be associated with sex determination (Hazzouri et al, 2019). Recently, Torres et al (2021) identified 16-bp male-specific sequences in the date palm Y chromosome. Date palms are facing a severe threat around the globe from red palm weevil (Rhynchophorus ferrugineus Olivier).…”
Section: Trait Marker Referencesmentioning
confidence: 99%
“…The 12th chromosome of the date palm has a higher SNPs density for gender discrimination than other chromosomes (Mathew et al, 2014). Moreover, there are reports of male-sterility mutations and female-suppressing mutation genes on the 12th chromosome (Torres et al, 2018;Torres et al, 2021).…”
Section: Introductionmentioning
confidence: 99%